2013
DOI: 10.4103/2231-0738.112839
|View full text |Cite
|
Sign up to set email alerts
|

Antieosinophilic activity of various subfractions of leaves of Vitex negundo

Abstract: Aim:The present study was undertaken to isolate and identify active constituent of leaves of Vitex negundo for their actions on bronchial hyperresponsiveness. Materials and Methods: Effects of aqueous subfraction, acetone subfraction, and chloroform sub-fraction on bronchial hyperresponsiveness and serum bicarbonate level were studied using egg-albumin-induced asthma in guinea pigs. The structure of aqueous subfraction of leaves of Vitex negundo was determined by various spectroscopy methods like UV spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…13,14 At the same time, the bronchodilatory property is partly explained by the presence of anti-eosinophilic activity of the leaves and the presence of papaverine-like phosphodiesterase inhibitors and diltiazem-like calcium channel blockers. 15,16 Overall, this investigation supports the previous studies of the cough relieving action of Lagundi. However, this is the first phase 3 randomized controlled trial to show that the effect of the capsule is comparable to the tablet.…”
Section: Discussionsupporting
confidence: 89%
“…13,14 At the same time, the bronchodilatory property is partly explained by the presence of anti-eosinophilic activity of the leaves and the presence of papaverine-like phosphodiesterase inhibitors and diltiazem-like calcium channel blockers. 15,16 Overall, this investigation supports the previous studies of the cough relieving action of Lagundi. However, this is the first phase 3 randomized controlled trial to show that the effect of the capsule is comparable to the tablet.…”
Section: Discussionsupporting
confidence: 89%
“…They successfully isolated a flavonoid compound, 5-hydroxy-3,6,7,3’,4’-pentamethoxyflavone (52) from the leaves and found that this compound potently suppressed eosinophil count in BALF (9.50 ± 1.5044; P < 0.05) in egg albumin-sensitized guinea pigs. This result was remarkable as the inhibition portrayed was comparable to that of dexamethasone control (7.50 ± 0.5014; P < 0.05) at a dose of 200 mg/kg (Patel and Deshpande, 2013). This is indicative of the potential of V. negundo in the treatment of allergy diseases like asthma.…”
Section: Suppression Of Eosinophils Migrationmentioning
confidence: 59%
“…This study showed that petroleum ether extract of Vitex negundo reduce bronchial hyper responsiveness, asthma and various inflammation, immunology, allergy diseases. 25…”
Section: Anti-snake Venom Activitymentioning
confidence: 99%